2004
DOI: 10.1021/jf049867x
|View full text |Cite
|
Sign up to set email alerts
|

Pectin Hydroxamic Acids Exhibit Antioxidant Activities in Vitro

Abstract: Commercial pectins with different degrees of esterification (DE) were reacted with equal volumes of 2 M alkaline hydroxylamine (pH 12.0) at room temperature for 4 h to prepare pectin hydroxamic acids (PHAs; DE94T4, DE65T4, and DE25T4) according to a previously reported method (Hou et al., J. Agric. Food Chem. 2003, 51, 6362-6366) and were used to test the antioxidant and antiradical activities in comparison with those of DE94, DE65, and DE25 pectins. The half-inhibition concentrations, IC(50), of scavenging ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Obviously, drying methods do have eff ects on DPPH radical-scavenging abilities and the DPPH radical-scavenging abilities of AP and SDP were higher than those of the ODP and FDP at all the same concentrations. Studies revealed that there was no signifi cant relationship between DPPH and pectin DE (Yang et al, 2004). The bioactivities of polysaccharides and their conjugates can be aff ected by many factors including chemical components, molecular mass, structure, conformation, and even the extraction and isolation methods (Xu et al, 2009).…”
Section: Scavenging Of Hydroxyl Radical By Pectin Treated By Diff Erementioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, drying methods do have eff ects on DPPH radical-scavenging abilities and the DPPH radical-scavenging abilities of AP and SDP were higher than those of the ODP and FDP at all the same concentrations. Studies revealed that there was no signifi cant relationship between DPPH and pectin DE (Yang et al, 2004). The bioactivities of polysaccharides and their conjugates can be aff ected by many factors including chemical components, molecular mass, structure, conformation, and even the extraction and isolation methods (Xu et al, 2009).…”
Section: Scavenging Of Hydroxyl Radical By Pectin Treated By Diff Erementioning
confidence: 99%
“…Epidemiological studies have shown that the consumption of fruits and vegetables is associated with a reduced risk of chronic diseases. It has been demonstrated that polysaccharides have strong antioxidant activities and this is because of the reduction power and free radical scavenging activities of these molecules (Yang et al, 2004;MateosAparicio et al, 2010;Tomida et al, 2010). Studies suggest that pectin can interact directly with oxidants and free radicals (Khasina et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The DPPH radical scavenging activities of the isolated pectin fractions were assayed according to the method described by Yang et al [25], with some modifications. The samples (in 50 mM Tris-HCl, pH 7.9) were mixed with the DPPH (Sigma-Aldrich) solution (130 M in ethanol) in a 1 : 1 ratio.…”
Section: Dpph (11-diphenyl-2-picrylhydrazyl) Radical Scavengingmentioning
confidence: 99%
“…Five concentrations of the substrate (15,20,25,50, and 100 M) were added after preincubating the enzyme with the inhibitor. The XO activities were determined in the presence of pectin fractions (0.25, 0.5, or 0.75 mg/mL) and ferulic acid (6.25, 12.5, or 18.75 g/mL).…”
Section: Determination Of the Type Of Xo Inhibitionmentioning
confidence: 99%
“…These ROS are formed under normal physiological conditions and may directly attack life important molecules such as membrane lipids, and initiate the pathogenic development of a number of aging-associated chronic human diseases such as cancers and coronary heart diseases [9,10].…”
Section: Esr In Radical Scavenging Capacity Examinationmentioning
confidence: 99%